PCRRT-ICONIC critical care pediatric nephrology course: the global prevalence of COVID-19 and associated sequelae - Raina, Rupesh; Vijayvargiya, Nina; Kalra, Riti; Yap, Hui-Kim; Nair, Nikhil; Alhasan, Khalid; Montini, Giovanni; Narang, Aarushi; McCulloch, Mignon; Bonilla-Felix, Melvin; Bagga, Arvind; Mok, Quen; et al. (Frontiers in Nephrology, 2022)
After nearly three years of the COVID-19 pandemic, research has affirmed that COVID-19 is more than just a respiratory virus. There have been significant breakthroughs made surrounding the development of acute kidney injury (AKI) and chronic kidney disease (CKD), in pediatric populations. Additionally, patient populations susceptible to renal complications consist of pediatric transplant recipients, multisystem inflammatory syndrome (MIS-C), and dialysis. Although research is gradually becoming more available surrounding this prevalent topic, knowledge is sparse on the deleterious effects of COVID-19 on pediatric patients with kidney disease and requires more in-depth analysis. The virtual international conference, Pediatric Critical Care Nephrology & Dialysis Course, on August 7th, 2021, reviewed the severe cases of COVID-19 in the global pediatric population. By integrating international perspectives, statistics, techniques, and treatments for managing renal complications, we further develop scientific understanding of the renal complications seen in children with COVID-19 globally.